2015
DOI: 10.1111/jan.12623
|View full text |Cite
|
Sign up to set email alerts
|

A mixed‐method study of effects of a therapeutic play intervention for children on parental anxiety and parents' perceptions of the intervention

Abstract: Therapeutic play intervention had no significant effect on parents' perioperative anxiety. Parents' and their children's perioperative anxiety are correlated. Parents perceived the intervention as helpful preparation for themselves and for their children undergoing elective surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 35 publications
1
30
0
4
Order By: Relevance
“…ZHU ET AL. | 1525 (Chieng, Chan, Klainin-Yobas, & He, 2014;Chieng et al, 2013;He, Zhu, Chan, Liam, et al, 2015;Noel, Chambers, McGrath, Klein, & Stewart, 2012b;Simons, 2015) and parents' anxiety is related to their children's anxiety and pain (Bearden, Feinstein, & Cohen, 2012;He, Zhu, Chan, Liam, et al, 2015). These aforementioned studies support the point that psychological and emotional factors affect patients' interpretations of their pain.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…ZHU ET AL. | 1525 (Chieng, Chan, Klainin-Yobas, & He, 2014;Chieng et al, 2013;He, Zhu, Chan, Liam, et al, 2015;Noel, Chambers, McGrath, Klein, & Stewart, 2012b;Simons, 2015) and parents' anxiety is related to their children's anxiety and pain (Bearden, Feinstein, & Cohen, 2012;He, Zhu, Chan, Liam, et al, 2015). These aforementioned studies support the point that psychological and emotional factors affect patients' interpretations of their pain.…”
Section: Discussionmentioning
confidence: 68%
“…Pain is not only a physiological process but also an affective experience influenced by physical and mental processes (Bernatzky, Presch, Anderson, & Panksepp, ; Renn & Dorsey, ). Several studies have revealed that children with higher state anxiety have more pain (Chieng, Chan, Klainin‐Yobas, & He, ; Chieng et al., ; He, Zhu, Chan, Liam, et al., ; Noel, Chambers, McGrath, Klein, & Stewart, ; Simons, ) and parents’ anxiety is related to their children's anxiety and pain (Bearden, Feinstein, & Cohen, ; He, Zhu, Chan, Liam, et al., ). These aforementioned studies support the point that psychological and emotional factors affect patients’ interpretations of their pain.…”
Section: Discussionmentioning
confidence: 99%
“…, He et al . ). None of the studies referred to methodological rigour of the qualitative element of the study insofar as there was not mention of transferability, auditability or creditability (Polit & Tanato Beck ).…”
Section: Resultsmentioning
confidence: 97%
“…One recent study, for example, He et al . (:1539), presented a ‘randomised controlled trial’ combined with a ‘qualitative process evaluation’. The intervention was a one‐hour therapeutic play for children that focused on pre‐operative preparation ( n = 92).…”
Section: Resultsmentioning
confidence: 99%
“…7 In the international literature, its use is highlighted as having a high therapeutic value for the child, contributing not only to physical improvement but also to the child's emotional well-being, 8 to reduction in pain and stress related to experiencing procedures such as venipuncture, 9 dressings, 10 inhalation therapies, 11 radiotherapy 12 and the preparation for surgery, 13,14 among others; it also has an effect on the reduction of the parents' anxiety, who come to understand this intervention's value. 15 Nevertheless, studies have not been identified related to the teaching of this strategy, it being the case that only one of these refers to the nurses' resistance regarding its use, due to their lack of familiarity with TP.…”
Section: Introductionmentioning
confidence: 99%